Analisis Komponen Makna Kata Bermakna ‘Berbicara’ dalam Bahasa Indonesia dan Bahasa Jawa - Desfiona, Elfara; Hardiasari, Shiva Arinda Putri; Qorizki, Deliza; Awaliyah, Sindi; Baehaqie, Imam (UNIB Press, 2025)
Language is a reflection of a society's culture and way of thinking. Each word has a unique meaning that includes not only the literal definition but also social and cultural values. “speaking” in Indonesian and its Javanese equivalent have different shades of meaning, even though both belong to the Austronesian language family. In Indonesian, “speaking” refers to conveying intentions or ideas orally, while in Javanese the meaning can vary depending on the level of language used. The researcher's aim is to explore the meaning of the word “speak” in Indonesian and Javanese and identify the differences and similarities between them. The researcher utilized a qualitative descriptive methodological approach and a theoretical approach. The data collection technique uses listening and note-taking techniques as well as the commensurate method with PUP basic technique and HBB advanced technique to analyze the data that has been obtained. The researcher differentiated the two languages with components of meaning differentiation based on objects in the form of one person and more than one person; volume in the form of whispering clearly and shouting; context in the form of anger, advising, and expressing; time in the form of a glimpse, a little long, and long; and distance in the form of near and far. The researcher differentiated the two languages with the components of meaning differentiation based on the object in the form of one person and more than one person; volume in the form of whispering clearly and shouting; context in the form of angry, advising, and expressing; time in the form of fleeting, rather long, and long; and distance in the form of near and far. The researcher obtained 34 speech data points that have the same meaning as